Improving The Professionalism of Bank Central Indonesia Managers Through Human Capital and Training - Iffah Budiningsih; Tjiptogoro Dinarjo Soehari; Alvita Sari (Research Synergy Foundation, 2023)
Employee professionalism is one of the behaviors that become the competitiveness of an institution in the global era. For that, employee professionalism behavior in strategic institutions must be continuously developed. This study aims to determine how high human capital and training factors influence the professional behavior of managers at Bank Central Indonesia in Jakarta. The research method used is the quantitative survey method with respondents at Bank Central Indonesia managers in Jakarta with a sample of 46 people from an affordable population of 108 managers (work experience above 20 years); the sample was taken by purposive quota sampling. Data collection using a questionnaire instrument with alternative answers of 5 (five) Likert scales. Data analysis using multiple regression with SPSS. The findings in this study are: a) human capital and training together influence the high and low development of managers' Â professional behavior; b) the relationship between human capital and training together to the professionalism of managers shows positive and very strong (R=0.833); Â c) human capital and training together contribute to the achievement of manager professionalism by 69.5%, and the remaining 30.5% by other factors; d) human capital has a higher sensitivity than training in the development of professionalism manager; e) ) in the digital era like today, the development of professional behavior is highly treated and can be done through strengthening human capital and organizing sustainable training.